Synergistic Effect of MC-LR and C-Terminal Truncated HBx on HepG2 Cells and Their Effects on PP2A Mediated Downstream Target of MAPK Signaling Pathway - Xiao, Chanchan; Mei, Fanbiao; Ren, Guanhua; Long, Long; Chen, Maojian; Fang, Xiang; Li, Jilin; Li, Kezhi; Tang, Yanping; Huang, Tianren; Deng, Wei (Frontiers in Genetics, 2020)
C-terminally truncated hepatitis B virus (HBV) X (ctHBx) infection and exposure to microcystins-LR (MC-LR) can lead to human hepatitis and liver cancer, but the mechanism associated with their synergistically effects not been fully elucidated. The ctHBx (HBxΔ4 and HBxΔ32) lentivirus were constructed and transfected into the HepG2 cells. Then we investigated the function of MC-LR and ctHBx using the molecular biology approaches, including enzyme-linked immunosorbent assay, clone formation assay, scratch wound testing, transwell assays, carried out flow cytometry respectively to examine cell cycle and apoptosis in each group, and detected the related proteins of HBx, MEK/ERK/JNK/p38 in mitogen-activated protein kinase (MAPK) pathway and the downstream proteins such as cdc2, cdc25C, and p53 by western blotting. We found that the protein phosphorylase 2A (PP2A) enzyme activity in MC-LR and HBxΔ32/HBxΔ4 groups decreased more than in MC-LR and HBx group at the same time point and MC-LR concentration (P < 0.05). Meanwhile the proliferation, migration, invasion and colony formation capability of HepG2 cells were significantly enhanced in MC-LR and ctHBx groups (P < 0.05). In addition the proportion of S stage cells in the MC-LR-treated HBxΔ32/HBxΔ4 groups was significantly greater than that in the untreated groups (P < 0.05). Furthermore, the protein expression of MAPK signaling pathway including phospho-MEK1/2, ERKl/2, p38, and JNK were up-regulated by MC-LR and HBxΔ32, and the expression of cyclin-related proteins, including p53, cdc25C, and cdc2 were also activated (P < 0.05). Taken together, our findings revealed the essential significance of the MC-LR and ctHBx on the PP2A/MAPK/p53, cdc25C and cdc2 axis in the formation and development of HCC and identified MC-LR and ctHBx as potential causal cofactors of hepatocarcinogenesis.